Ṭuruq Tadrīs al-Lugah al-‘Arabiyyah li al-NāṭIqīn bi Gairiha - Muhammad Muhlisin (ALSINATUNA, 2015)
Becoming a professional Arabic teacher needs knowledge, skills, accuracy, strategy, and perseverance. Besides that, a professional teacher of Arabic also needs interesting methods in the teaching and learning process. There are so many teaching methods used in the foreign language teaching and learning. However, some of them are not appropriate to be used. Each of them has strengths and weaknesses, so it is better for a foreign language teacher, especially Arabic teacher not to rely on one method only, but he should choose and determine the appropriate methods which is relevant with the learning material in order to create fun learning process.